PENGEMBANGAN PEMBELAJARAN PENDIDIKAN AGAM ISLAM MELALUI PENDEKATAN INTERDISIPLINER DI SEKOLAH MENENGAH ATAS (SMA) - Surohim Surohim (Program Studi Pendidikan Agama Islam Fakultas Agama Islam Univesitas Muhammadiyah Bengkulu, 2023)
The industrial era 4.0 demands that educational institutions must be able to transform into all-digital institutions, as the assumption does not rule out the possibility that with the rapid progress of science and technology there will be global changes and will affect the values, attitudes or behavior of students' lives and modern society, it could be These values, attitudes and behaviors are in line with the teachings of Islam and support the success of development. On the other hand, it could be contrary to the teachings of Islam and even do not support the success of development, such as weak religious beliefs, individualistic, materialistic, hedonistic attitudes. criticisms of the weaknesses of the implementation of Islamic religious education in schools, such as (1) in the field of theology, there is a tendency towards fatalistic understanding. (2) The field of worship is only taught as a routine religious activity and is not emphasized as a process of personality formation, (3) the field of morals is oriented towards politeness and has not been understood as a whole religious human person, (4) the field of fiqh tends to be taught as a boundary of governance. rules that will not change over time, and do not understand the dynamics and spirit of Islamic law, (5) Islam tends to be taught as a dogma and does not develop rationality and love for science and technology advances, (6) the orientation of studying the Qur'an still tends to on the ability to read texts, has not led to understanding meaning and extracting meaning. There needs to be positive and reactive innovation towards the Islamic religious education learning system so that it becomes more effective, namely through an interdisciplinary approach. This interdisciplinary approach in Islamic religious education is able to bring a new atmosphere for students to keep trying to learn so that noble ideals are achieved. Islamic religious education with an interdisciplinary approach has been able to change the form and way of learning Islamic religious education from classical learning to modern learning.Keywords: Islamic Education Learning, Interdisciplinary Approach, Learning Effectiveness